Usefulness of Alcohol-screening Instruments in Detecting Problem Drinking among Elderly Male Drinkers - Ryou, Young Il (The Korean Academy of Family Medicine, 2012)
BACKGROUND: In Korea, few studies have been performed on screening instruments for the detection of at-risk drinking and alcohol use disorders in the elderly. This study evaluated the validity of three screening instruments in elderly male drinkers. METHODS: The subjects were 242 Korean men aged ≥ 65 years. Face-to-face interviews were used to identify at-risk drinking and alcohol use disorders. At-risk drinking was defined according to the criteria for heavy or binge drinking of the National Institute on Alcohol Abuse and Alcoholism. Alcohol use disorder was diagnosed using the criteria of the Diagnostic and Statistical Manual of Mental Disorders IV-text revision. The Alcohol Use Disorder Identification Test (AUDIT), Short Michigan Alcoholism Screening Test-geriatric version (SMAST-G), and cut down, annoyed, guilty, eye-opener (CAGE) questionnaire were used as the alcohol-screening instruments. Based on the diagnostic interview results, sensitivity, specificity, and area under the receiver operating characteristic curve (AUROC) of the instruments were compared. RESULTS: For identification of at-risk drinking, the AUDIT AUROC demonstrated greater diagnostic power than did those of SMAST-G and CAGE (both P < 0.001). In screening for alcohol use disorders, the AUDIT AUROC was also significantly higher than those of SMAST-G and CAGE (both P < 0.001). The sensitivity and specificity of screening for at-risk drinking with an AUDIT score ≥ 7 were 77.3% and 85.1%, respectively, whereas those for the alcohol use disorders with an AUDIT score ≥ 11 were 91.3% and 90.8%, respectively. CONCLUSION: The results suggest that the AUDIT is the most effective tool in identifying problem drinkers among elderly male drinkers.